Time of Motor Response To Stimuli (Auditory and Visual) and Its relationship with Blocking Accuracy In Volleyball - Fadel, Muneer; Mansoor, Samer (Journal of Physical Education, 2020)
The research aim at identifying the time of motor response to auditory and visual stimuli as well as identifying the accuracy of blocking and finding the relationship between motor repose time and blocking accuracy. The community was (7) primer soccer league of 2019 – 2020 and the subjects were (24) volleyball players from Al Jaish and Al Shorta clubs ten players from Al Shorta club performed the pilot study. The researchers used the descriptive method and the data was collected and treated using SPSS. The results showed a significant relationship between response time and blocking accuracy. The researchers recommended concentrating on applying scientific principles for developing time of motor response in a manner suitable for blocking in volleyball as well as the necessity of developing time of motor response that directly affect defensive skills of volleyball players.